(untitled) (Research, Society and Development, 2025)
This research aims to provide a transformative learning epistemology in the Merdeka Belajar Kampus Merdeka (MBKM) curriculum in Indonesia. This curriculum has been implemented since 2021. This curriculum allows university students to gain learning experience outside campus for three semesters. This curriculum is relevant to the concept of transformative learning. Epistemologically, students are not only required to understand the object being studied, but also, in their own way, find new perspectives and understanding of the object being studied. This research is qualitative research using a philosophical perspective, especially in the epistemological aspect. Epistemology studies aim to look for things related to knowledge, such as sources of knowledge, processes, criteria for truth and validation. This research concluded that transformative learning and MBKM are philosophically related, especially with regard to human ontology as free being. Freedom learning is well adopted in transformative learning strategies. In this strategy, the role of the lecturer is only to present the object of knowledge, create an actual atmosphere, and then let students discover knowledge in their own way. In implementing MBKM, this transformative learning strategy still has several challenges, including: student learning habits that still depend on lecturers or data sources, and lecturers’ lack of knowledge about techniques for implementing transformative learning. However, overall, this transformative learning strategy is very suitable to be applied in higher education, because as adult learners, students must be able to use their minds and reasoning to gain knowledge and understanding in their own way.